Research on shale dynamic and static elastic modulus and anisotropy based on pressurization history - Zhang, Di; Li, YaFeng; Guo, YaNan; Xia, HanLin; Liu, YanXin; Yan, JiaShen; Wang, Fei; Wu, YinTing (Frontiers in Earth Science, 2025)
The dynamic and static elastic parameters of rocks exhibit differences. It is of great practical significance to carry out experiments on dynamic and static elastic parameters of rocks under reservoir conditions and determine the conversion relationship between dynamic and static elastic parameters. In this study, shale oil samples from the second member of Kongdong sag in Dagang Oilfield were analyzed by triaxial compression experiments at different bedding angles and longitudinal and shear wave velocity tests. Dynamic and static stiffness coefficient, elastic modulus and acoustic wave velocity change under different directions of pressure and pressure relief. The results indicate that the P-wave velocity, fast shear wave velocity, slow shear wave velocity, dynamic and static Young’s modulus exhibit an increase as the confining pressure rises, and the parameters are greater during the unloading process than during loading process. At identical confining pressures, the dynamic Young’s modulus measured by cores with parallel bedding plane is greater than that measured by cores with vertical bedding plane. The dynamic and static elastic mechanical parameters of different bedding angles can be transformed under varying pressures, and the dynamic elastic mechanical parameters measured under varying levels of confining pressure can be transformed into static elastic mechanical parameters under equivalent confining pressures, which offer fundamental parameters for examining rock mechanics properties and serving as a reference for developing fracturing construction plans for oil and gas reservoirs.